2013
DOI: 10.1371/journal.pone.0056703
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Traditional Chinese Medicine for Diabetes: A Double-Blind, Randomised, Controlled Trial

Abstract: BackgroundTreatment of diabetes mellitus with Traditional Chinese Medicine has a long history. The aim of this study is to establish the safety and efficacy of traditional Chinese medicine combined with glibenclamide to treat type 2 diabetes mellitus.MethodsIn a controlled, double blind, multicentre non-inferiority trial, 800 patients with unsatisfactory glycemic control (fasting glucose 7–13 mmol/L and HbA1c 7–11%) were randomly assigned to receive Xiaoke Pill, a compound of Chinese herbs combined with gliben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 14 publications
4
80
0
3
Order By: Relevance
“…The therapeutic effect of this TCM on diabetes or DN has been identified by previous studies (33)(34)(35). The present study demonstrated that SKC-YJ treatment is effective in improving clinical syndromes, including reducing proteinuria, blood glucose levels, HBAlc, blood lipids and blood viscosity, as well as increasing the serum albumin level.…”
Section: Discussionsupporting
confidence: 72%
“…The therapeutic effect of this TCM on diabetes or DN has been identified by previous studies (33)(34)(35). The present study demonstrated that SKC-YJ treatment is effective in improving clinical syndromes, including reducing proteinuria, blood glucose levels, HBAlc, blood lipids and blood viscosity, as well as increasing the serum albumin level.…”
Section: Discussionsupporting
confidence: 72%
“…In diabetes patients, TCM herbs such as Rhizoma Coptidis, Radix Rehmanniae Recens, Radix Ginseng, Radix Puerariae, Radix Astragali seu Hedysari, Radix Bupleuri, Radix et Rhizoma Rhei, Radix Scutellariae, Radix Trichosanthis, Fructus Mume and Rhizoma Anemarrhenae have been shown to effectively lower blood glucose and improve clinical outcomes. We assessed 12 RCTs that focused on TCM and diabetes and had the following Jadad scores: 7 (six reports), 6 (one report), 5 (four reports) and 4 (one report). Sample sizes ranged from 79 to 800, and follow‐up duration ranged from 12 to 48 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Xiao Ke Wan is a fixed dose combination drug containing glyburide and various TCMs that have the antihyperglycaemic effect similar to that of glyburide. Compared with glyburide alone, Xiao Ke Wan carries a lower risk of hypoglycaemia …”
Section: Pharmacologic Therapy For Hyperglycaemiamentioning
confidence: 99%